Ocular Manifestations of Migraines and Their Clinical Implications in the Optometric Setting. - Cercone, Jocelyn (Optometry & Visual Performance, 2015)
Ocular manifestations of migraines can present in many modalities other than the traditional visual aura. This review describes the current theories of migraine pathophysiology, emphasizing the relationship between the brain and the vascular system. Many variations of visual field defects, retinal anomalies, and other neuro-ophthalmic conditions may present with migraine. A significant association exists between migraines and normal tension glaucoma, which may influence our treatment and management of patients exhibiting these two conditions. Migraine sufferers often show symptoms of visual discomfort out of proportion to those experienced by the general population, even when they are not experiencing a migraine. Through administration of the pattern glare test, optometrists can better isolate individuals particularly affected by these visual triggers and manage them through the use of ophthalmic tints designed to reduce symptoms of discomfort. Conditions like transient ischemic attacks and epilepsy can often present in similar ways to visual aura, so recognizing subtle differences in presentation becomes particularly important when managing patients complaining of visual symptoms.